The nexus between analytical skills, employment relations and future workspace - Schultz, Cecile M. (Advances in Social Sciences Research Journal, 2020)
Little research, if any, has been conducted on management’s expectations from their human resource management related to the nexus between analytical skills, employment relations and future workspace. The purpose of this study is to determine if there is a correlation between perceived analytical skills, employment relations and future workspace. A survey research design and a quantitative approach were utilised. The general managers of the human resource managers that were affiliated with the South African Board of People Management completed the questionnaire. Correlation analyses was used to analyse the data. The results indicated that there was a significant positive relationship between analytical skills, employment relations and future workspace. The results contributed new insights obtained from the views of management and their future expectations from HR in relation to analytical skills, employment relations and future workspace. The study is noteworthy in that its results may be used to make substantial decisions to improve the HR’s analytical skills and employment relations due to its relationship with future workspace.